Study on Static Foam Stabilization and its Properties - Bathe, G. A.; Tadvi, Aasma R. (Scientific Research, New Technologies and Applications Vol. 5, 2024)
Surfactant foams find wide-ranging uses in several industrial domains, such as chemical and biological processes and products. To improve the foam's stability, the static foam behaviour has been examined in this chapter. For a variety of surfactants, the characteristics of static foam, including percentage foamability and foaming power, have been studied. It was observed that SLS shows the highest percentage of foamability (77.72%) when compared with CTAB and SLS. Studies have also been conducted on the effects of pH on static foam. The pH range of 9 to 11 causes the foam half-life to drop from 125 minutes to 75 minutes. Effects on the foam behaviour due to the addition of small amounts of volatile components (VOCs) such as ethanol, xylene, toluene, and so forth were also investigated. The role of nanoparticles (NPs) in static foam and liquid drainage from the foam section is discussed in detail. Static foam properties were also investigated for the combined use of various surfactants.